Waste-derived volatile fatty acids as carbon source for added-value fermentation approaches. Issue 9 (24th May 2021) - Chalima, Angelina; de Castro, Laura Fernandez; Burgstaller, Lukas; Sampaio, Paula; Carolas, Ana Lúcia; Gildemyn, Sylvia; Velghe, Filip; Ferreira, Bruno Sommer; Pais, Celia; Neureiter, Markus; Dietrich, Thomas; Topakas, Evangelos
ABSTRACT: The establishment of a sustainable circular bioeconomy requires the effective material recycling from biomass and biowaste beyond composting/fertilizer or anaerobic digestion/bioenergy. Recently, volatile fatty acids attracted much attention due to their potential application as carbon source for the microbial production of high added-value products. Their low-cost production from different types of wastes through dark fermentation is a key aspect, which will potentially lead to the sustainable production of fuels, materials or chemicals, while diminishing the waste volume. This article reviews the utilization of a volatile fatty acid platform for the microbial production of polyhydroxyalkanoates, single cell oil and omega-3 fatty acids, giving emphasis on the fermentation challenges for the efficient implementation of the bioprocess and how they were addressed. These challenges were addressed through a research project funded by the European Commission under the Horizon 2020 programme entitled 'VOLATILE—Biowaste derived volatile fatty acid platform for biopolymers, bioactive compounds and chemical building blocks'. Abstract : Waste valorization: volatile fatty acids for the microbial production of bioplastics, single-cell oil and omega-3 fatty acids.